The Impact of Family Issues on Students’ Academic Performance - Bhatt, Nisha; Bhatt, Jayanti (Brixton Scholarly Review, 2026)
The aim of this study is to investigate the impact of family-related factors on the academic performance of college students in Mahendranagar. This research employed a quantitative cross-sectional research design. The data were collected using a structured questionnaire from 85 respondents. Financial status, parental behavior, and family environment were considered independent variables. Academic performance was considered the dependent variable. The results show that financial status has a strong positive correlation with academic performance (r = 0.600, p < 0.01), along with moderate positive correlations between parental behavior (r = 0.508) and family environment (r = 0.509). Additionally, financial status was found to significantly predict academic performance in the regression analysis (β = 0.403, p < 0.001). On the other hand, there is no statistical significance observed with respect to parental behavior (p = 0.273) and family environment (p = 0.567). The R² value of the model indicates that the model explains 40.4% of the variance of academic performance. The study indicates that financial stability has a major influence on academic performance, while family-related psychosocial factors have an indirect influence. The study highlights the need to address financial issues for better academic performance of students.